2004
DOI: 10.1021/ac049396d
|View full text |Cite
|
Sign up to set email alerts
|

Electrokinetically Controlled DNA Hybridization Microfluidic Chip Enabling Rapid Target Analysis

Abstract: Biosensors and more specifically biochips exploit the interactions between a target analyte and an immobilized biological recognition element to produce a measurable signal. Systems based on surface nucleic acid hybridization, such as microarrays, are particularly attractive due to the high degree of selectivity in the binding interactions. One of the drawbacks of this reaction is the relatively long time required for complete hybridization to occur, which is often the result of diffusion-limited reaction kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
66
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(66 citation statements)
references
References 65 publications
0
66
0
Order By: Relevance
“…Due to their miniaturization and automation, there are a number of advantages of using microfluidic systems, such as less sample/reagent consumption, reduced risk of contamination, less cost per analysis, lower power consumption, enhanced sensitivity and specificity, and higher reliability. Microfluidic systems have been developed for various biological analytical applications, such as DNA analysis [4][5][6][7][8], immunoassay [9][10][11][12][13], and cell analysis [14][15][16][17][18]. Moreover, a number of demonstrations showed that cell culture can be performed on the microfluidic systems to achieve higher throughput and more reliable results [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their miniaturization and automation, there are a number of advantages of using microfluidic systems, such as less sample/reagent consumption, reduced risk of contamination, less cost per analysis, lower power consumption, enhanced sensitivity and specificity, and higher reliability. Microfluidic systems have been developed for various biological analytical applications, such as DNA analysis [4][5][6][7][8], immunoassay [9][10][11][12][13], and cell analysis [14][15][16][17][18]. Moreover, a number of demonstrations showed that cell culture can be performed on the microfluidic systems to achieve higher throughput and more reliable results [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Another limitation of the surfacebased DNA hybridization assays is the relative long time for hybridization reaction, typically requires several hours or more because it generally depends solely on the diffusion of target DNA to the surface-bound probes (Jobs et al 2002). However, Erickson et al (2004) introduced an electrokinetically controlled DNA hybridization microfluidic chip based on surface DNA hybridization. They utilized electroosmotic driven flow in their system to deliver samples/reagents, which increased the reaction rate.…”
Section: Surface Probe-based Dna Hybridization Assaysmentioning
confidence: 99%
“…With the rapid growth of the microfluidic technology, microarrays and microfluidic biochips have been extensively employed as promising tools for DNA analysis over the past decade (Berti et al 2009;Cao et al 2010;Chen et al 2008;Heule and Manz 2004;Javanmard and Davis 2011;Mai et al 2007;Mulvaney et al 2007;Jin et al 2009;Kwakye and Baeumner 2003;Li and He 2009;Senapati et al 2009). The advantages of applying microfluidics platform in DNA hybridization have been demonstrated in many representative works (Fan et al 1999;Erickson et al 2004;Ali et al 2003;Sun and Kwok 2006;Ferguson et al 2009). It has been demonstrated that the ability to do DNA analysis with micrometre resolution facilitates the realization of a functional hybridization assay (Lange et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These devices were integrated into a single chip and worked cooperatively to perform a specific assay. Various biological analytical applications, such as DNA analysis, [24][25][26] immunoassay, [27][28][29][30] and cell analysis, [31][32][33][34] have been demonstrated using microfluidic systems. For example, a microfluidic-based DNA analysis system integrated with microchannels, heaters, temperature sensors, and fluorescence detectors was capable of capturing the DNA, mixing the solutions together, amplifying the DNA, and separating and detecting those products.…”
Section: Introductionmentioning
confidence: 99%